2022
DOI: 10.3390/ph15020238
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Pharmacological Activities Bouea macrophylla Griffith In Vivo and In Vitro Study: A Review

Abstract: Bouea macrophylla Griffith (B. macrophylla) is one of the many herbal plants found in Asia, and its fruit is plum mango. This plant is rich in secondary metabolites, including flavonoids, tannins, polyphenolic compounds, and many others. Due to its bioactive components, plum mango has powerful antioxidants that have therapeutic benefits for many common ailments, including cardiovascular disease, diabetes, and cancer. This review describes the evolution of plum mango’s phytochemical properties and pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 150 publications
(179 reference statements)
0
10
0
Order By: Relevance
“…B. macrophylla seed, a by-product from fruit consumption and processing, has been reported for its several biological properties and secondary metabolites 9) . However, there is no information regarding the ameliorative effect of B. macrophylla seed extract against bacteria-induced acne inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B. macrophylla seed, a by-product from fruit consumption and processing, has been reported for its several biological properties and secondary metabolites 9) . However, there is no information regarding the ameliorative effect of B. macrophylla seed extract against bacteria-induced acne inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, B. macrophylla contains seeds presenting purple cotyledons which are wastes from processing and consumption. Noticeably, previous studies widely reported that B. macrophylla seed is a rich source of antioxidants 9) . Furthermore, the seed extracts derived from ethanolic extraction and its aqueous formations exerted a notable antioxidant, antimicrobial, anti-aging, and anticancer effects owing to their polyphenol components 8,9) .…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…These mixtures might be answerable for the pharmacological potential of Bouea macrophylla as an antioxidant [ 1 ], antimicrobial, anticancer [ 3 ], antihyperglycemic, and antiphotoaging [ 4 ] agent. Consumption of Bouea macrophylla fruit can also increase the β-carotene concentration in the blood [ 5 ]. However, data on this fruit are still limited and the safety efficacy, particularly in toxicological studies, is still under-explored [ 5 ].…”
Section: Introductionmentioning
confidence: 99%